An NADPH‐Dependent Ketoreductase Catalyses the Tetracyclic to Pentacyclic Skeletal Rearrangement in Chartreusin Biosynthesis. (5th November 2021) - Jiao, Fang Wen; Wang, Yi Shuang; You, Xue Ting; Wei, Wanqing; Chen, Yu; Yang, Cheng Long; Guo, Zhi Kai; Zhang, Bo; Liang, Yong; Tan, Ren Xiang; Jiao, Rui Hua; Ge, Hui Ming
Abstract: Redox tailoring enzymes play key roles in generating structural complexity and diversity in type II polyketides. In chartreusin biosynthesis, the early 13 C‐labeling experiments and bioinformatic analysis suggest the unusual aglycone is originated from a tetracyclic anthracyclic polyketide. Here, we demonstrated that the carbon skeleton rearrangement from a linear anthracyclic polyketide to an angular pentacyclic biosynthetic intermediate requires two redox enzymes. The flavin‐dependent monooxygenase ChaZ catalyses a Baeyer–Villiger oxidation on resomycin C to form a seven‐membered lactone. Subsequently, a ketoreductase ChaE rearranges the carbon skeleton and affords the α‐pyrone containing pentacyclic intermediate in an NADPH‐dependent manner via tandem reactions including the reduction of the lactone carbonyl group, Aldol‐type reaction, followed by a spontaneous γ‐lactone ring formation, oxidation and aromatization. Our work reveals an unprecedented function of a ketoreductase that contributes to generate structural complexity of aromatic polyketide. Abstract : The rearrangement from the tetracyclic to the pentacyclic compound in the biosynthesis of the antitumor antibiotic chartreusin is very concise and only requires two redox enzymes. ChaZ mediates a Baeyer–Villiger oxidation to give a lactone intermediate. Subsequently, ChaE catalyses an unusual ketoreduction on an ester carbonyl group to give an acetal moiety, followed by a series of spontaneous reaction to construct the pentacyclic compound.